Synthesize Iron Oxide and Zinc Oxide Nanoparticles Using Plant Extracts - Dalal Ibrahim; Karema Abdelghani; Safa Anwagy; Rowedah Rizkallah (AlQalam Journal of Medical and Applied Sciences, 2024)
Recently, a plant-mediated approach to synthesizing nanoparticles via unconventional, eco-friendly technique-based techniques involving natural materials was developed. In this work, the microwave method has been used, where Hibiscus rosa sinensis flower extract and Myristica Fragrans have been used as reducers and stabilizers to synthesize iron oxide nanoparticles (α-Fe2O3) and zinc oxide nanoparticles (ZnO), respectively. The melting point and ultraviolet-visible spectrometer (UV-Vis) have been utilized to investigated and characterized the synthesized iron oxide and Zinc oxide nanoparticles. The results showed that the melting point of Fe2O3-NPs and ZnO-NPs were above 300 °C, which indicated the melting of nanoparticle. Nanoparticles exhibit a significant in melting point as their size goes below ≈10 nm. in addition, the UV-Vis absorption spectra of the synthesized iron oxide NPS show peak surface plasmon resonance (SPR) band around 320 nm and Zinc oxide NPS shown peak surface plasmon resonance (SPR) band around 370 nm. The microwave method has been successfully used in this study, which has advantages over the other methods. في الآونة الأخيرة، تم تطوير النهج النباتي لتصنيع الجسيمات النانوية عبر تقنيات غير تقليدية وصديقة للبيئة تعتمد على مواد طبيعية. في هذا العمل، تم استخدام طريقة الميكروويف، حيث تم استخدام مستخلص زهرة الكركديه الوردية وجوز الطيب لتصنيع جسيمات أكسيد الحديد النانوية (α-Fe2O3) وجسيمات أكسيد الزنك النانوية (ZnO) على التوالي. تم استخدام درجة الانصهار ومطياف الأشعة فوق البنفسجية المرئية (UV-Vis) لفحص وتوصيف الجسيمات النانوية لأكسيد الحديد وأكسيد الزنك. وأظهرت النتائج أن درجة الانصهار Fe2O3-NPs وZnO-NPs كانت أعلى من 300 درجة مئوية تقريبًا، مما يشير إلى تكوين الجسيمات النانوية. تظهر الجسيمات النانوية ارتفاعا كبيرًا في درجة الانصهار حيث يقل حجمها عن ≈10 نانومتر. بالإضافة إلى ذلك، يُظهر أطياف امتصاص UV-Vis لجسيمات أكسيد الحديد النانوية نطاق ذروة رنين البلازمون السطحي (SPR) حوالي 320 نانومتر وجسيمات أكسيد الزنك النانوية يظهر نطاق ذروة رنين البلازمون السطحي (SPR) حوالي 370 نانومتر. لقد تم استخدام طريقة الميكروويف بنجاح في هذه الدراسة، والتي تتمتع بمزايا مقارنة بالطرق الأخرى